PERBANDINGAN ANALYTICAL ANISOTROPIC ALGORITHM (AAA) DAN PENCIL BEAM CONVOLUTION (PBC) UNTUK PERENCANAAN DISTRIBUSI DOSIS RADIASI BOOSTER KANKER SERVIKS - RAIH RIZKY MEGA FALAH, 081113040 (2018)
This study aims to determine the comparison of Analytical Anisotropic Algorithm (AAA) and Pencil Beam Convolution (PBC) for planning the distribution of radiation booster doses in cervical cancer patients. A dose calculation simulation was performed using a treatment planning system (TPS)Eclips brand Varian model 11.0.0 in six cervical cancer patients who received radiation booster planning. The dose given is 2 Gy with 10 fractions. Selected box fields techniques with gantry angles at 00, 900, 1800, and 2700 used a 6 MV Linac energy machine. This study uses homogeneity index (HI) and conformity index (CI) as parameters to compare the calculations of AAA and PBC.